Hyperhomocysteinemia-induced VCID results in visual deficits, reduced neuroinflammation and vascular alterations in the retina - Erica M. Weekman; Colin B. Rogers; Tiffany L. Sudduth; Donna M. Wilcock (Journal of Neuroinflammation)
Abstract Over recent years, the retina has been increasingly investigated as a potential biomarker for dementia. A number of studies have looked at the effect of Alzheimer’s disease (AD) pathology on the retina and the associations of AD with visual deficits. However, while OCT-A has been explored as a biomarker of cerebral small vessel disease (cSVD), studies identifying the specific retinal changes and mechanisms associated with cSVD are lacking. Using our model of hyperhomocysteinemia-induced cSVD, we aimed to identify the effects of cSVD on visual sensitivity and cognition, retinal glial and vascular cells, and neuroinflammatory and cardiovascular gene expression changes. We placed C57Bl6/SJL mice on a HHcy-inducing diet, a model that has been well characterized to have vascular pathologies in the brain similar to pathologic cSVD. After 14 weeks on diet, mice underwent the Visual-Stimuli 4-arm Maze to identify visual deficits. Whole mount retinas were stained for vessels, microglia and astrocytes to identify glial and vascular changes. Finally, neuroinflammatory and cardiovascular gene expression was measured using NanoString’s nCounter system. Ultimately, HHcy led to visual changes that specifically affected the reaction to blue and white light, slightly decreased vascular volume and significantly decreased interaction of microglia with the vasculature, as well as downregulation of inflammatory and vascular genes. These changes provide novel insights and reproduce some prior observations. These studies highlight retinal changes in association with cSVD and serve as a precaution when interpreting vision-dependent cognitive testing of cSVD models.